Beyond the Black Box: Towards a Theology of the Artifact and the Phronetic Validation of AI-Mediated Liturgy in Madagascar - Nomenjanahary Jenny Patrick; Robijaona Rahelivololoniaina Baholy (Matondang Journal, 2027)
This study investigates the ontological and methodological transition from Paul Tillich’s classical correlation to a paradigm of Augmented Correlation within the liturgical context of the Fiangonan’i Jesoa Kristy eto Madagasikara (FJKM). Facing the dual pressures of temporal scarcity and the need for theological depth, this research proposes the "LiturgIA" framework—a hybrid architecture synchronizing the high-reasoning capabilities of the DeepSeek R1 model with specialized symbolic knowledge bases, including original biblical lexicons (HALOT, BDAG) and local hymnological corpora. The innovative core of this work lies in its "Five-Episteme Model," which orchestrates a disciplined dialogue between biblical theology, computer science, practical theology, sociology, and systematic theology. Empirical results demonstrate a transformative efficiency, yielding an 89% reduction in liturgical preparation time while simultaneously increasing the Theological Coherence Index (TCI). Unlike traditional "black-box" systems, the model utilizes Chain-of-Thought (CoT) reasoning to bridge the "Explainability Gap," ensuring that algorithmic suggestions remain subject to "epistemic vigilance." By grounding the AI in 200 historical programs and Malagasy-specific hymnals, the study successfully counters digital colonialism, preserving liturgical sovereignty and inculturation. Ultimately, the research affirms that while AI masters tekhnê (technical optimization), the human pastor remains the indispensable arbiter of phronêsis (practical wisdom). This "augmented" approach transforms artificial intelligence into an "exegetical orthosis," supporting the structural integrity of the proclamation without infringing upon the "algorithmic unavailability" of the inner sanctuary or the pneumatological event of worship.